Wound specific quality of life after blast or gunshot injury: Validation of the wound QoL instrument - Andreas Älgå; Jonas Malmstedt; Ann-Mari Fagerdahl (PLoS ONE, 2022)
Background Acute blast or gunshot wounds have a negative effect on the patients’ health related quality of life (HRQoL). No validated instrument exists to assess the HRQoL of patients with such wounds. Therefore, we aimed to test and validate a subscale of an existing HRQoL instrument among patients with acute blast or gunshot wounds. Methods We used data from a randomized controlled trial comparing negative pressure wound therapy with standard treatment of civilian adults with acute extremity blast or gunshot wounds. We evaluated the reliability (internal consistency, stability) and validity of the body subscale of the Wound QoL instrument using the World Health Organisation 20 question self-reporting questionnaire as gold standard. Results A total of 152 participants were included in the study. The participants were predominantly (93.4%) male, and median age was 29.0 years (IQR 21.0–34.0). The internal consistency was acceptable while a test-retest analysis indicated instability in the Wound QoL instrument. The content validity of the instrument was considered satisfactory; however, the criterion validity was found to be insufficient. Conclusions Our results indicate that Wound QoL is a promising instrument for the assessment of wound specific HRQoL among patients with acute blast or gunshot wounds. Further testing and validation is needed.